2018
DOI: 10.1111/trf.14538
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence, immunogenicity, and evanescence of alloantibodies to MUT and Mur antigens of GP.Mur red blood cells in a Southeast Asian patient cohort

Abstract: Antibodies to MUT and Mur develop following multiple RBC exposures. Immunogenicity of MUT/Mur and evanescence rates of the corresponding antibodies is higher compared to anti-E. Appropriate selection of antibody screening cells is needed in view of the high prevalence, immunogenicity, and evanescence of the antibodies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The antigens in the MNS blood group system expressed from hybrid glycophorins A and B (formerly known as the Miltenberger series) are such an example, many of which are prevalent among Southeast Asians. 6 We found anti-Mi a in a patient with a pregnancy ABBREVIATIONS: DAT = direct antiglobulin test; GA = gestational age; HDFN = hemolytic disease of the fetus and newborn; MCA = middle cerebral artery; PSV = peak systolic velocity. history that included spontaneous losses and a stillborn from her eighth pregnancy that, in retrospect, had physical features of hemolytic disease of the fetus and newborn (HDFN).…”
Section: Case Presentationmentioning
confidence: 85%
See 3 more Smart Citations
“…The antigens in the MNS blood group system expressed from hybrid glycophorins A and B (formerly known as the Miltenberger series) are such an example, many of which are prevalent among Southeast Asians. 6 We found anti-Mi a in a patient with a pregnancy ABBREVIATIONS: DAT = direct antiglobulin test; GA = gestational age; HDFN = hemolytic disease of the fetus and newborn; MCA = middle cerebral artery; PSV = peak systolic velocity. history that included spontaneous losses and a stillborn from her eighth pregnancy that, in retrospect, had physical features of hemolytic disease of the fetus and newborn (HDFN).…”
Section: Case Presentationmentioning
confidence: 85%
“…Alloimmunization to hybrid A/B glycophorin antigens is reported to be approximately 0.3% in Southeast Asia . The morbidity and mortality risk to the newborn and subsequent pregnancies are significant, as is the management and postnatal options as outlined to this patient.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mur are typically associated with hemolytic transfusion reaction and hemolytic disease of the fetus and newborn,[ 7 8 9 10 33 ] and these antibodies are commonly found in East and Southeast Asian populations. [ 10 34 35 36 37 ] In Malaysia, a retrospective study showed that the antibodies to MNS variants (Mi a , MUT, and Mur antigens) increased from 0.94% (2004–2008 years) to 5.82% (2009–2010 years). [ 38 ] In another study, anti-MUT and anti-Mur were detected in alloimmunized patients with a prevalence of 5.0% and 0.7%, respectively.…”
Section: Discussionmentioning
confidence: 99%